Comparison of Universal Plan Indices for Intensity Modulated Radiotherapy of Head and Neck Cancer treatment - B. Rekha Reddy; Ravikumar M.; C.R. Tanvir Pasha; C. Varatharaj (International Journal of Medical Research and Review, 2018)
Objective: Manual evaluation of IMRT plans for head-and-neck cancers has been especially challenging necessitating efficient and objective assessment tools. Based on previous clinical experience, the radiation oncologists prescribe the dose to the tumour after critical evaluation of the dose to critical structures. We have evaluated the IMRT plan using Universal Plan Indices and Quality factor.Methods and Materials: In the Eclipse Treatment Planning Systems, we have selected 15 head and neck cancer patients who underwent IMRT delivery in sliding window mode at Clinac DHX linear accelerator equipped with a 120 leaves MLC. All patients were treated using 6 MV photon beams. The UPI indices and Quality factor were calculated using HART software based on MATLAB background.Results: The mean conformity numbers for all fifteen patients were found as 0.92±0.05 and the mean target volume ratio was 1.02±0.04. Similarly the other indices like DG, NCI and modified HI index were 0.95±0.03, 1.08±0.06 and 0.94±0.02 respectively. The mean overall quality factor was found to be 1.01±0.02. The typical value of this factor also to be unity and above unity referred to be overdosed and below the unity referred as under dosage of the structures contoured volume in the corresponding plan.Conclusion: Hence, we have concluded that, evaluation of the IMRT plan of head and neck cancer patients using Universal plan Indices and Quality factor have been done successfully using HART software